INDONESIA AND ASEAN+ GREEN VS NON-GREEN HOSPITAL PERFORMANCE COMPARISON - Gunawan, Indra; Achsani , Muhammad; Faisal, Yudi Ahmad; Fajri, Muhammad (Faculty of Economic and Business, University of Pasundan, 2025)
The aim of this study is to compare the financial performance of a sample of green hospitals and non-green hospitals in Indonesia and ASEAN+. Statistical time series methods used to analyse compiled data from time to time that enables to identify trends and patterns that happened in a data series. For the green hospital, the position of the majority financial ratio in green hospital in Indonesia is higher than non-green hospital in all period. The other way around is happening with financial ratio in hospitals in South East Asia where non-green hospitals are performing better in all periods except 2021. The result delineates that green hospital becomes the pioneer in facing climate change and creating a sustainable environment for the society. This study adds the existing literature of green economy from a quantitative perspective in ASEAN region.